A Novel Quantitative Fluorescent Reporter Assay for RAG Targets and RAG Activity - Trancoso, Ines; Bonnet, Marie; Gardner, Rui; Carneiro, Jorge; Barreto, Vasco M.; Demengeot, Jocelyne; Sarmento, Leonor M. (Frontiers in Immunology, 2013)
Recombination-Activating Genes (RAG) 1 and 2 form the site specific recombinase that mediates V(D)J recombination, a process of DNA editing required for lymphocyte development and responsible for their diverse repertoire of antigen receptors. Mistargeted RAG activity associates with genome alteration and is responsible for various lymphoid tumors. Moreover several non-lymphoid tumors express RAG ectopically. A practical and powerful tool to perform quantitative assessment of RAG activity and to score putative RAG-Recognition signal sequences (RSS) is required in the fields of immunology, oncology, gene therapy and development. Here we report the detailed characterization of a novel fluorescence-based reporter of RAG activity, named GFPi, a tool that allows measuring recombination efficiency by simple FACS analysis. GFPi can be produced both as a plasmid for transient transfection experiments in cell lines or as a retrovirus for stable integration in the genome, thus supporting ex vivo and in vivo studies. The GFPi assay faithfully quantified endogenous and ectopic RAG activity as tested in genetically modified fibroblasts, tumor derived cell lines, developing pre B cells and hematopoietic cells. The GFPi assay also successfully ranked the recombination efficiency of various RSS pairs, including bona fide RSS associated with V(D)J segments, artificial consensus sequences modified or not at specific nucleotides known to affect their efficiencies, or cryptic RSS involved in RAG-dependent activation of oncogenes. Our work validates the GFPi reporter as a practical quantitative tool for the study of RAG activity and RSS efficiencies. It should turn useful for the study of RAG mediated V(D)J and aberrant rearrangements, lineage commitment and vertebrate evolution.